Construction of sacrificial network in styrene-ethylene/butadiene-styrene triblock copolymer composites and their mechanical behaviors. Issue 12 (2nd December 2021) - Liao, Tingting; Wu, Jianyu; Tang, Zilun; Su, Qiuping; Huang, Zhiyi; Gu, Yuxin; Li, Yong; Xie, Jing; Lin, Xiaofeng; Yi, Guobin
Abstract: Herein, benefiting from effective energy-dissipation mechanism, the high-performance thermoplastic elastomers (ZASM/SEBS composites) with excellent mechanical strength-toughness combination were prepared by blending 3-Amino-1, 2, 4-triazole (ATA), maleic anhydride grafted styrene-ethylene/butadiene-styrene triblock copolymer (SEBS-g-MA), zinc acetate and styrene-ethylene/butadiene-styrene triblock copolymer (SEBS) successively. The Zn 2+ -carboxyl coordination and hydrogen bonding dual-dynamic network of composites was proved by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. The mechanical performance of ZASM/SEBS composites was investigated by tensile test. With the decreasing mass ratio of ZASM in ZASM/SEBS composites, the tensile strength and elongation at break increased firstly and then decreased. When the mass ratio of ZASM in composites was 30%, the tensile strength reached 32.1 MPa along with the elongation at break of 1383%, attaining the best mechanical strength-toughness combination. It is demonstrated that the ZASM/SEBS composites could be a promising substitute for traditional vulcanized rubber. Graphical Abstract: UF0001